1991
DOI: 10.1139/y91-128
|View full text |Cite
|
Sign up to set email alerts
|

Vascular effects of some opioid receptor agonists

Abstract: Opioid peptides have been implicated in shock-associated hypotension. Our aim was to find out whether opioid agonists have direct vasodilator actions on vascular smooth muscle. The study was conducted on rat abdominal aortic rings. In rings precontracted with either norepinephrine, prostaglandin F2 alpha, or high potassium Krebs (HPK), the effects of the opioid agonists tested (morphine, U50488H, ethylketocyclazocine (EKC), and bremazocine) depended on the precontracting agent used. HPK-precontracted rings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…The main finding of these studies is that intra‐arterial infusion of morphine causes a dose‐dependent vasodilatation in the human forearm. A number of investigators have also previously demonstrated the direct vasodilator action of opioids in animal vessels [14–16]. This response was not subject to acute tolerance and persisted for a period of at least 1 h after the end of the morphine infusion.…”
Section: Discussionmentioning
confidence: 88%
“…The main finding of these studies is that intra‐arterial infusion of morphine causes a dose‐dependent vasodilatation in the human forearm. A number of investigators have also previously demonstrated the direct vasodilator action of opioids in animal vessels [14–16]. This response was not subject to acute tolerance and persisted for a period of at least 1 h after the end of the morphine infusion.…”
Section: Discussionmentioning
confidence: 88%
“…In isolated rat tail veins, Illes et al (38) showed that U50,488H and ethylketocyclazocine depressed stimulation-induced contraction while naloxone (10 cLM> did not prevent such actions. In abdominal aortic strips, contractions induced by either 1 p i 4 norepinephrine or 10 prostaglandin F,, were potentiated by low concentrations (0.1-10 N) of U50,488H, but were depressed by high concentrations (50 and 100 w) (19). Verapamil(6 w) reduced the inhibitory effect of high concentrations of U50,488H.…”
Section: Mechanisms Involved In the Nonopioid Actions Of Kappa Agonistsmentioning
confidence: 96%
“…These effects are attributable to inhibition of sympathoadrenal outflow as demonstrated by reductions in plasma levels of norepinephrine (34). El-Sharkawy and colleagues performed in vitro experiments that generated evidence of the direct effects of bremazocine (32) and other opioid agonists (9) on vascular smooth muscle. The effects of the agents varied depending on the agonist used, the concentration tested, and the pre-contracting agent used.…”
Section: Cardiovascular Effectsmentioning
confidence: 99%